Professional expectations of Peruvian medical interns and their inclination for primary health care - Ramírez, Marco (2008)
Introduction: Current availability of human resources in health is within international standards, but in our country distribution is not equitable and in inverse relation with central health problems. Objective: To determine professional expectations of medical interns and their inclination for primary health care. Design: Descriptive and transversal study, with randomized systematic sampling. Setting: Five Lima and Callao’s national hospitals, during 2006. Par ticipants: Two hundred and seven medical interns. Interventions: Application of a self-administered questionnaire. Results: Specialization represented in 84,5% the most valuable and priority training and professional practice option for medical interns. Most wished specialties were surgical in 37% and clinical in 30%. Also 30% of future physicians planned to work in a foreign country. There was significant statistical association between procedence from a public university and the desire to specialize in our country, as well as, coming from a private university and wishes to specialize abroad. Finally 25,1% of the interns manifested they would do primary health care. Conclusions: There existed high expectative in doing a specialty in medical interns interviewed in this study, mainly in surgery, as well as predisposition to work in a foreign country, with little preference in first level health service.